الأساليب النتهجة لتحليل التكاليف في المؤسسة الإقتصادية - دنيا زاد بن والي, رجاء خثير (My University, 2022)
In order for the institution to achieve its economic goals, it uses many means and methods related to management. In this field, analytical accounting is the most suitable means used that help in analyzing and controlling costs, and this is by providing information that contributes to controlling these costs and in order to apply analytical accounting procedures, the path must be familiar Sufficient financial and economic issues in the organization, so there must be an accounting system that includes management rules and determines the scope of their application, so that this system is one of the sources from which analytical accounting derives its credibility. Selling them and delivering them to customers, and the development of this system is often important and useful in terms of the interest obtained from the system. The institution relies on studying the various methods that allow it to make correct decisions, namely: the real cost method, the variable cost method, the rational assumption of 97 fixed costs.The following :- Rational loading of fixed costs are variable costs per unit and fixedvolumeof activity; - Variable costs are fixed costs per unit and variable volume of activity
دراسة حالة ملبنة مستغانم
Keywords: Analytical accounting, burdens and costs, cost analysis